2018
DOI: 10.33549/physiolres.933962
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate Metabolites in Maternal and Cord Plasma and Their Relations to Other Selected Endocrine Disruptors and Steroids

Abstract: Endocrine disruptors (EDs) are known to have harmful effects on the human endocrine system; special effort is actually given to the exposure during pregnancy. Humans are usually exposed to a mixture of EDs, which may potentiate or antagonize each other, and the combined effect may be difficult to estimate. The main phthalate monoesters monoethyl-, mono-n-butyl-, monoisobutyl-, monobenzyl-, mono-(2-ethylhexyl)-, mono-(2-ethyl-5-hydroxyhexyl)- and mono-(2-ethyl-5-oxohexyl) phthalate were determined in 18 materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 68 publications
(57 reference statements)
1
15
0
1
Order By: Relevance
“…The effects of maternal phthalate exposure on fetal reproductive hormones are conflicting. Maternal plasma phthalate levels during pregnancy in the third trimester were negatively correlated with cord blood DHEA, androstenedione, and testosterone, while positively associated with estradiol and estriol (31). However, associations between maternal serum MEHP levels and the high levels of DHEA and high ratios of DHEA/androstenedione in cord serum were reported later (32).…”
Section: Prenatal Phthalate Exposure and Fetal And Neonatal Sex Hormonesmentioning
confidence: 84%
See 1 more Smart Citation
“…The effects of maternal phthalate exposure on fetal reproductive hormones are conflicting. Maternal plasma phthalate levels during pregnancy in the third trimester were negatively correlated with cord blood DHEA, androstenedione, and testosterone, while positively associated with estradiol and estriol (31). However, associations between maternal serum MEHP levels and the high levels of DHEA and high ratios of DHEA/androstenedione in cord serum were reported later (32).…”
Section: Prenatal Phthalate Exposure and Fetal And Neonatal Sex Hormonesmentioning
confidence: 84%
“…Reproductive system is the main targets of phthalates, especially in males. Multiple research studies have reported the associations between intrauterine phthalate exposure and reproductive hormones in cord blood (29)(30)(31)(32) and amniotic fluid (33), which provided evidence that maternal phthalate exposure could affect fetal sex steroid hormones status. The explanation for this may be that phthalates disrupt the function of Leydig and Sertoli cells in testis (4).…”
Section: Prenatal Phthalate Exposure and Fetal And Neonatal Sex Hormonesmentioning
confidence: 99%
“…Similarly, bisphenol S (BPS) causes a failure of microtubule formation and disrupts cumulus cells expansion (Zalmanova et al 2017). The impact of endocrine disruptors on newborn steroidogenesis was shown in a study of Kolatorova et al (2018), which confirmed accumulation of phthalate in the fetal area via measurements in maternal plasma and in the cord blood of their newborns. These facts taken together have a significant impact on quality of oocytes and success of human reproduction.…”
Section: Granular Cells As Targets Of Environmental Toxinsmentioning
confidence: 60%
“…Several animal studies have been conducted to examine the deleterious effects of various environmental toxicants on male fertility and decipher their possible mechanism(s) of action (Akarca-Dizakar et al, 2019;Albert, Nardelli, Lalancette, Hales, & Robaire, 2018;Aydin & Erkan, 2017;Campos et al, 2019;Kim, Cheon, Choi, & Lee, 2019;Kolatorova et al, 2018). The focus of this review is to shed light on the impact of environmental contaminants on male reproduction and the underlying mechanism of action based on the recent scientific data available.…”
mentioning
confidence: 99%